Penggunaan Metode Problem Based Learning Untuk Meningkatkan Minat Belajar Siswa Pada Pelajaran Fiqih - Nur, Lutfiyah; Setiawan, Hasrian Rudi (Journal of Sustainable Education, 2025)
Students' interest in learning jurisprudence in class XI is often still low, resulting in a less optimal learning process and understanding of the material. This problem is caused by learning methods that are less interesting and less actively involving students. To overcome this, this research examines the use of the Problem Based Learning (PBL) method as an alternative learning strategy that solves problems collaboratively. The Poblem Based Learning method is applied by giving students real problems that must be solved and solved in groups, thus creating an active and participatory learning atmosphere. Data was obtained through observation, in-depth interviews, and documentation during the learning process. Data analysis is done descriptively to understand changes in students' interest in learning in depth. The results of the research show that the application of Poblem Based Learning can significantly increase students' interest in learning, as evidenced by the high participation, enthusiasm, and positive response of students during jurisprudence learning. This finding confirms that the Problem Based Learning method is effective in motivating and increasing student engagement, as well as enriching the learning experience in jurisprudence subjects.